A Comprehensive Analysis of the Influence of Fly Ash on the Bond Properties between Reinforcing Steel and Concrete - - ADNAN; Muhammad ANAS (Journal of Materials and Engineering Structures)
This paper examines the possible use of fly ash to make concrete greener. Because cement manufacturing adds to CO₂ levels, using fly ash instead is becoming more popular. This study seeks to find out how bond strength changes for 0–30% fly ash replacement, study the effects of microstructure, and establish the best ratios for use in structures. For this experiment, we used Grade 53 OPC concrete, which was made to meet a target strength of 20 MPa with a water-binder ratio of 0.5. On-center compressive strength (ASTM C39), tensile strength (ASTM C496), and bond strength (ASTM C900) were tested. The study showed that using a 10% fly ash replacement resulted in the best outcome, raising the concrete’s compressive strength by 7.3% (from 22.3 to 23.6 MPa), tensile strength by 5% (4.2 MPa), and bond strength by 3% (13.9 MPa) by pozzolanic reactions at the interface between aggregates and cement. When the quantity of added fly ash was increased to 20–30%, the concrete became weaker and difficult to work with (slump: 0–0.9 in.), again due to fly ash diluting the binder. We found out that 10% is the most sustainable amount of fly ash for construction. We had used superplasticizers with silica fume when we were going to replace the amount of cement. In the future, experiments with added salt, carbonation, and earthquake loads could extend how widely this approach is used.